Spiritual Well-Being Of Health Failure Patients - Agung Maulana Yusuf; Tuti Pahria; Aan Nuraeni (Journal of Nursing Care, 2019)
Introduction: Decreasing heart function raises problems both physical, psychological and spiritual. Patients faced this health issue, and they need an individual’s spirit and encouragement related to self- management and illness. The purpose of this study was to describe the spiritual well-being of heart failure patients. Method: The method used in the research was a quantitative descriptive method with a cross-sectional approach. The population in this research was all patients with heart failure who underwent inpatient and outpatient care. Samples were taken by consecutive sampling technique for one month and 61 respondents were obtained. Data were collected by using the Spirituality Index of Well-Being instruments. Univariate data analysis uses the mean values and frequency distribution. Result: The result showed that patients with heart failure who had high spiritual well-being were 53 people (86,9%). In life scheme sub-variable, 55 people (90,2%) were included in the high category. In self-efficacy sub-variable, 48 people (78,7%) were included in high category but 13 people (21,3%) were into the low category with a low mean score of 3 statements. Conclusion: almost all respondents have high spiritual well-being reinforced by life scheme but there is a part of self-efficacy that still needs to be improved such as the knowledge about how to overcome the burden of life, the ability to help themselves, and the understanding related to the disease. Therefore, it is important to give information related to the patient’s illness to improve the patients’ spiritual well-being which can affect the health condition of the patient. In addition, physical, psychological and social management also have an important role in improving self-efficacy.